All‐cause hepatocellular carcinoma survival in the era of direct‐acting antiviral therapy. Issue 12 (30th September 2021) - Lockart, Ian; Hajarizadeh, Behzad; Buckley, Niamh; Davison, Scott; Prakoso, Emilia; Levy, Miriam T; George, Jacob; Dore, Gregory J; Danta, Mark
Abstract: Background and Aim: Hepatitis C virus (HCV) cure with direct‐acting antiviral (DAA) therapy improves survival in patients with HCV‐related hepatocellular carcinoma (HCC). We hypothesized that HCV‐HCC survival has increased in the DAA era, more than other aetiologies of HCC. We aimed to evaluate survival following HCC diagnosis in the pre‐DAA and DAA eras, across each aetiology of HCC. Methods: Patients with HCC at three tertiary referral hospitals were included retrospectively (January 2008 to December 2019). Patients were categorized as HCV‐HCC, hepatitis B virus (HBV)‐HCC, or non‐viral HCC. For each aetiology, the risk of death following incident HCC among patients diagnosed in the DAA era (2015–2019) was compared with patients diagnosed in the pre‐DAA era (2008–2014). Results: Among 1161 patients, there were 422 (36%) patients with HCV‐HCC, 227 (20%) with HBV‐HCC, and 512 (44%) with non‐viral HCC. In adjusted analysis, the risk of death was lower in patients with HCV‐HCC diagnosed in 2015–2019, compared with patients diagnosed in 2008–2014 (adjusted hazard ratio [aHR]: 0.68; 95% confidence interval [CI]: 0.52–0.89; P = 0.005). In contrast, there was no difference in the risk of death between time periods for patients with HBV‐HCC (HR: 0.91; 95% CI: 0.64–1.29; P = 0.602) or non‐viral HCC on adjusted analysis (aHR: 0.92; 95% CI: 0.74–1.15; P = 0.476). Although patients with HBV‐HCC had better survival compared with patients with HCV‐HCC in 2008–2014 (aHR: 0.74; 95% CI: 0.55–0.98; P = 0.037), this difference disappeared in 2015–2019 (aHR: 1.26; 95% CI: 0.90–1.77; P = 0.175). Conclusions: Hepatitis C virus‐related HCC survival has increased in the DAA era, whereas adjusted survival remained stable for HBV‐HCC and non‐viral HCC.